Automotive Technician Certification Test Prepartion Manual - Knowles Don (Thomson Delmar Learning, 2006)
Filled with updated task list theory, practice tests, and abundant, demonstrative graphics, this revised edition provides all the latest information required to sufficiently prepare technicians to pass each of the A1-A8 and L1 ASE certification exams. Each chapter begins with a pretest that indicates the depth of preparation required to become familiar with the information in the chapter, followed by a description of each ASE task and the must-have information related to the task. ASE-type questions at the end of each chapter appear in the same format as on actual ASE tests to further prepare users to pass each exam.